Suitability of testers to characterize provitamin a content and agronomic performance of tropical maize inbred lines - Maazou, Abdoul-Raouf Sayadi; Adetimirin, Victor O.; Gedil, Melaku; Meseka, Silvestro; Mengesha, Wende; Menkir, Abebe (Frontiers in Genetics, 2022)
Vitamin A deficiency poses health risks for children, pregnant women, and nursing mothers in sub-Saharan Africa (SSA) and Southeast Asia. Provitamin A–biofortified maize varieties can contribute to minimizing the adverse effects of vitamin A deficiency in areas where maize is a staple food crop. Identifying suitable testers is important to breed provitamin A–biofortified hybrid maize. This study was therefore conducted to 1) assess the suitability of maize inbred lines with contrasting levels of provitamin A (one with high and one with low provitamin A concentration) to assess the combining ability of maize inbred lines in accumulating provitamin A and other carotenoids, and grain yield, 2) confirm the mode of inheritance of provitamin A and grain yield, and 3) identify promising inbred lines with desirable combining ability effects for use to develop high-yielding provitamin A–biofortified hybrids. The inbreds crossed to the two inbred testers were evaluated in four environments for the carotenoid content and eight environments for the agronomic performance. The combined analysis of variance revealed a significant genetic variation among the testcrosses for all carotenoids, grain yield, and other agronomic traits. The mode of inheritance for grain yield, other agronomic traits, provitamin A, and other carotenoids was regulated by both additive and non-additive gene effects with a prominence of additive gene effects. The high provitamin A tester that displayed positive GCA effects for β-carotene and provitamin A content, broader agronomic performance of testcrosses, and higher levels of provitamin A in testcrosses can be considered suitable for breeding programs developing provitamin A–biofortified hybrids. The inbred lines TZI2012, TZI2142, TZI2130, TZI2065-2, TZI2161, TZI2025, TZI1278, TZI1314, TZI1304, and TZI2032 with positive GCA effects for grain yield and provitamin A content could be used as parental lines to develop source population of new inbred lines and high-yielding hybrids with elevated levels of provitamin A. The best performing hybrids are promising for release as high-yielding provitamin A maize hybrids after further evaluations.